Shattered : a high risk novel - Ross, JoAnn (Signet, 2009)
More than a year after his affair in Baghdad with Army doctor Kirby Campbell, Army pilot Shane Garrett is trying to rebuild his life stateside. Kirby is also stateside, but when she learns a friend is being held hostage in Central America, she works with Phoenix Team to organize a rescue.